Ragam Doa dan Azimat Keselamatan dalam Naskah Mujarobah - Sa'dudin, Ihsan (IAIN Syekh Nurjati Cirebon, 2024)
Prayer is a medium of communing with God. A prayer with a specific purpose has a certain kaifiyah or procedure, either done before or after the prayer. In certain conditions, kaifiyah and other media are needed so that the prayer is easily granted, such as reciting the Prayer of Sulaiman nine times to be kept away from wild animals and the heat of the fire, and burning coconuts while reciting the prayer of Sulaiman eight times to get a melodious voice. This article aims to analyze the prayers contained in the manuscript LKK_CIAMIS2013_MLM01. This manuscript contains prayers and talismans for healing and salvation written in Arabic and explanations of prayers using Sundanese and Javanese. The philological method and content analysis were used in order to get an overview of the characteristics of the content, make an interpretation of the content, and identify something that appears. The research data were analyzed using Miles and Huberman's theory, namely reduction, data display, and conclusion drawing. The results of this study show that the manuscript LKK_CIAMIS2013_MLM01 contains prayers and talismans with certain kaifiyah and efficacy.